Who do they think we are? Public perceptions of psychiatrists and psychologists. (2nd January 2018) - Patel, Krisna; Caddy, Caroline; Tracy, Derek K
ABSTRACT: Objective: Psychiatrists and clinical psychologists assess and treat individuals with a wide-range of mental health needs, and the differences between them are not always well understood by other professionals or the public. Most work on perceptions in mental health has evaluated issues such as diagnosis, risk, prognosis, and blame. Little has evaluated and contrasted broader perceptions of psychiatrists and psychologists. We qualitatively explored views of members of the public, in order to identify such wider understanding. Method: Nine individuals with no experience of mental ill-health were interviewed using a semi-structured interview guide. Transcripts were thematically analysed. Results: Three core themes were identified: perception of roles, stigma, and increasing future awareness. There was frequent misunderstanding of these professions. In general, however, psychiatrists were seen as more authoritarian and with a medication focus, though their interventions were believed to be effective. Psychologists were perceived as friendlier and having a better rapport, though participants thought they only typically looked at 'minor' difficulties. Discussion: Public perceptions matter. There is a lack of clarity in the public mind about our roles. These data should aid professionals' self-reflection of potential transference issues, and to consider local applicability and variation of our findings. The two professions should consider public psychoeducatative programmes to inform and encourage engagement. Abstract :